Determinant Factors of Anemia in Pregnant Women at Kebomas Health Center - Eka Puspitasari, Dyan; Katmini, Katmini (Journal of Maternal and Child Health, 2023)
Background: The period of pregnancy is when the body really needs maximum food intake, both physically and spiritually. This study aimed to examine the effect of nutritional intake, trust, and iron consumption compliance on anemia in pregnant women at the Kebomas Health Center. Subjects and Method: This was cross-sectional study in the Kebomas Health Center Work Area. A sample of 168 pregnant women was selected by simple random sampling. The dependent variable was anemia. The independent variables were nutritional intake, trust, and iron consumption compliance. The data were collected by the questionnaire and analyzed by multiple logistic regression. Results: Anemia in pregnant women increased with poor nutritional intake (aOR= 19.52; 95% CI= 14.87 to 38.37; p= 0.001), less trust (aOR= 18.37; 95% CI= 13.34 to 36.09; p= 0.001), and inadherent to iron consumption (aOR= 14.82; 95% CI= 10.28 to 27.34; p <0.001). Conclusion: Anemia in pregnant women increases with poor nutritional intake, less trust, and inadherent to iron consumption. Keywords: nutrition intake, compliance, anemia. Correspondence: Dyan Eka Puspitasari. Master’s Program in Public Health, Strada Indonesian Institute of Health Sciences. Jl. Manila No. 37, Kediri 64133, East Java, Indonesia. Email: dyanekapuspitasari@gmail.com. Mobile: +628123129993.